The Effect of the Landa Model on Academic Achievement among Eighth Grade Female Students in Social Studies Geography a study extracted from a master`s thesis - امین, چاوان علی حمە امین حمە; خالد, آ.م.د. ڕزگار حمە لاو خالد (Sulaimani Journal for Humanities, 2025)
The aim of this study is to investigate the effect of the Landa instructional model on the academic achievement of eighth-grade of basic education students in social science/geography. The researcher employed a quasi-experimental design with two equivalent groups. The total sample consisted of 36 students, divided into two groups: an experimental group of 18 students who were taught using the Landa model, and a control group of 18 students who were taught the same subject using traditional instructional methods. The study was conducted at Kurd genius Basic School. Equivalence between the two groups was ensured based on the following variables: students’ scores in social science from the previous academic year, age, level of intelligence, parents’ educational level, and prior knowledge, assessed through a pre-test.To determine the content to be taught during the experimental phase, the researcher selected three units from the social science textbook. A total of 69 learning objectives were formulated based on Bloom’s taxonomy, covering the cognitive levels of (recall, comprehension, application, and analysis). Instructional plans were prepared for both groups accordingly. Afterwards, the researcher designed an achievement test to measure students’ academic performance. The test consisted of (35) items, including (25) multiple-choice questions and (10) essay-type questions, constructed based on a table of specifications. To ensure the validity of the tools, they were submitted to a group of experts. For reliability, the test–retest method was used. Data were analyzed using the SPSS statistical package. The results revealed a statistically significant difference in the mean scores between the experimental and control groups, in favor of the experimental group. This indicates that the Landa model had a positive impact on students’ academic achievement. In light of the findings, the study concludes that the Landa instructional model is effective in improving student performance in social studies. The study presents several conclusions and offers practical recommendations to enhance teaching strategies. Let me know if you would like this formatted into an abstract or if you need assistance preparing it for publication or presentation
Keywords: Landas strategy; Academic achievement; Social materials; Students